Clinical characteristics of 2, 459 severe or critically ill COVID-19 patients: A meta-analysis. Issue 5 (5th February 2021) - Zhong, Zhimei; Li, Hongyuan; Zhu, Jieyun; Ji, Pan; Li, Bocheng; Pang, Jielong; Zhang, Jianfeng; Liang, Xiangdong
Abstract : Abstract: Our study aims to summarize the clinical characteristics of patients with severe or critically ill coronavirus disease 2019 (COVID-19). Five databases were electronically searched to collect studies describing clinical characteristics of severe or critically ill COVID-19 patients and published between January 1, 2020 and April 12, 2020. Three reviewers independently collected the literature, extracted the required data, and assessed the risk of publication bias of the included studies before including the studies in the meta-analysis. A total of 40 studies involving 2459 patients with severe or critically ill COVID-19 patients were included. Meta-analysis showed that a greater proportion of severe or critically COVID-19 patients were male (62.3%), and the 2 main clinical symptoms were fever (87.4%) and cough (66.3%). Other common clinical symptoms included dyspnea (45.3%), chest tightness (37.4%), fatigue (36.6%), and expectoration (31.9%). Minor symptoms included myalgia (19.5%), dizziness (11.5%), headache (11.4%), diarrhea (11.2%), pharyngalgia (11.0%), nausea, and vomiting (5.9%). Most patients showed elevated levels of C-reactive protein (83.5%) and D-dimer (73.3%), lymphopenia (70.3%), and normal leukocyte counts (56.9%). Other findings included abnormal levels of liver function (39.8%), elevated procalcitonin (36.6%), leukocytosis (21.7%), thrombocytopenia (19.0%), and leucopenia (18.2%). Most patients showed acute respiratory distress syndrome (60.8%). Other complications included acute cardiac injury (37.1%), shock (32.0%), and acute kidney injury (22.0%). The most common symptoms of severe or critically ill COVID-19 patients were fever and cough. Most patients showed lymphopenia, elevated levels of C-reactive protein and D-dimer. A large percentage of patients progress to ARDS, acute cardiac injury, acute kidney injury and shock were also common.